PhD summary: Minority voting and representation: The impact of religion, migration background and gender on voter preferences for in- and out-group politicians in France, Germany and the Netherlands - van Oosten, Sanne (Politics of the Low Countries, 2025)
The political representation of historically marginalised and minoritised groups is far from straightforward. Minoritised politicians often distance themselves from their group to broaden their electoral appeal (Stephens-Dougan, 2020). Meanwhile, party elites also struggle with dilemmas of inclusion (Dancygier, 2017) leading to political representation of minoritised groups characterised as suppressing instead of supporting (Aydemir & Vliegenthart, 2016, 2022). In light of this convoluted context, how do voters react to diversity in politics? I studied how voters react to women, ethnic minority, and Muslim politicians, as well as how these groups respond to in-group politicians.